Implementasi enterprise resource planning (ERP) berbasis odoo pada modul inventory - Adviant Novita (Qualitative Research of Business and Social Sciences, 2023)
Accounting information systems are the core of management information systems, which are essential in various industrial sectors. Technology and software such as Enterprise Resource Planning (ERP) are used to maximize information management. PT JSI is a service company that has the potential to utilize technology to increase operational efficiency. Even though it has the potential to utilize technology, manual processes in managing inventory and delays in financial reports are the main obstacles. Therefore, implementing the Odoo inventory module can be a solution to overcome obstacles in managing business processes related to warehouse operations. This research aims to analyze the business processes of PT JSI's inventory division by implementing the Odoo ERP system, evaluate the impact of implementing the inventory module on inventory management, and measure the level of user acceptance of the Odoo ERP system. The research was conducted for three months using a qualitative descriptive approach, collecting primary data from interviews, observations, and secondary data from internal company sources and related literature. The research results show the transformation of PT JSI's manual business processes into integrated ones by implementing ERP Odoo, enabling data storage between divisions in one database. Configuring the Odoo inventory module makes it easier to create purchase invoices, check stock, and reduce the risk of transaction errors and financial calculations. Inventory division users welcomed the Odoo ERP implementation for inventory activities at PT JSI.